Profil Pemecahan Masalah Matematika Siswa MA Salafiyah Menganti Ditinjau Dari Tipe Kepribadian - Stani, Dwinta; Tristanti, Lia Budi; Iffah, Jauhara Dian Nurul (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
The purpose of this study was to describe the math problem solving profile of MA Salafiyah Menganti students in terms of introverted personality type and extroverted personality type. This research method uses descriptive qualitative. The results showed (1) introverted students in identifying known data, asked by being silent first, writing symbols according to what they understand, when making a mathematical model the subject pays attention to the problem given, writing the method used using elimination followed by substituting, the subject is seen solving the problem in detail and structured, solving the problem looks focused and working sequentially according to the steps, (2) extroverted students in identifying known and questionable data, by notwriting sentences, but only circling the problem and reading aloud, the subject spontaneously wrote symbols in the form of variables, the subject made a mathematical model by writing the equation, the subject revealed thestrategy by substitution, in applying the strategy.